Dimensions of Conscious Consumption: Focussing responsible consumption regarding other people’s interests - Dudás, Katalin (The Hungarian Journal of Marketing and Management, 2019)
Enlightened consumer, conscious consumption, sustainable consumption, ethical consumption, responsible consumer, social responsibility, environmental consciousness, ethnocentrism, etc. There are numerous concepts in marketing literature and practice on consumers’ consciousness. Definitions of these concepts are often ambiguous or overlapping. The aim of this study is to identify real contents of these concepts and to find out the relationships among them; with the use of the Hungarian and the international marketing literature and a qualitative depth interview research.